Effect of Hydrophobic Carbon Chain Length on the Crystal Structure of MCM-41 - 张光旭 陶玲 张高勇 (Chinese journal of chemical engineering, 2008)
The mesoporous molecular sieve （MCM）-41 using ionic liquid as template has been prepared. The typical template of ionic liquid was [C16mim]X. In this article, the use of 1-alkyl-3-methylimidazolium （[Cnmim]Br, where n= 12,14,16,18,20） salts as templates in the synthesis of MCM-41 is reported. The results showed that the synthesized MCM-41 had uniform pore diameter, high surface area and stable framework. The largest surface area of MCM-41 was the one prepared with [C14mim]Br as template. When using [C18min]Br as template, the narrowest pore distribution sample was obtained and the effect of surface tension of template solution to MCM-41 was first discussed.